An Analysis Of Medicine Inventory Accounting Information System At Mentiring Health Center On Psap Number 5 - Vesti Septina Putri; Ahmad Soleh; Kamelia Astuty (Penerbit Jurnal Indonesia, 2023)
This study aims to find out whether the application of the accounting information system that has been implemented in managing drug supplies is running in accordance with PSAP Number 5 and meets the needs at Mentiring Health Center. The type of data used in this research is qualitative comparative data, which is research carried out by comparing a variable in different samples to get answers or facts about whether there is a comparison or not from the research. Data was obtained from field studies through observation, interviews, documentation. The results of the research carried out show that the procedures for implementing the drug inventory accounting system at Mentiring Health Center, the implementation of the drug supply accounting system uses a first-in, first-out (FIFO) system, first-in, first-out and first expired first out (FEFO), but the accounting system and procedures implemented are not yet effective and efficient. This happens because the records used are still manual records so that physical drug inventory data has a very large risk of data damage. Manual records are still carried out because community health center staff are not yet proficient in using computer-based records and are also hampered by the internet network which is difficult to access.